Women characters in Arthurian literature - Kopřivová, Monika (2007)
The thesis will explore women characters in Arthurian literature, namely in Geoffrey of Monmouths History of the Kings of Britain, Chrétien de Troyes Arthurian Romances, and Thomas Malorys Morte dArthur. It will then follow some of their recreations through the ages in Tennysons Idylls of the King and Marion Zimmer Bradleys The Mists of Avalon. It will be subsequently attempted to trace the development of these women characters in relation to the position of women in the different eras